Diversity of Dengue Virus Serotypes in Dhaka City: From 2017 to 2021 - Rahim, Rummana; Hasan, Abu; Hasan, Nazmul; Nakayama, Emi E; Shioda, Tatsuo; Rahman, Mizanur (Bangladesh Journal of Medical Microbiology, 2021)
This is a retrospective observational study aimed to search the alteration of circulating dengue virus (DENV) serotypes in Dhaka City for five consecutive years (2017-2021) along with disease outcome. Methods: Routine dengue NS1 or PCR positive dengue samples from patients who visited Evercare Hospital Dhaka (ex. Apollo Hospitals Dhaka) were selected for serotype determination by serotype specific real time reverse transcriptase PCR (RT-PCR). Results: In 2017, predominant serotype was DENV-2 (91.3%) with less than 5% of DENV-1 and DENV-3 among 161 cases. In 2018, among127 cases, DENV-2 was the predominant serotype (40.95%) followed by DENV-3 (33.07%) and DENV-1 (25.98%). In 2019, predominance of DENV-2 was totally replaced by DENV-3 (91.86%) and DENV-1 (8.14%). In 2021, only DENV-3 serotype was detected among 178 samples. Regarding serotype association with disease outcome, more severe cases (Dengue Hemorrhagic Fever/Dengue Shock Syndrome) were observed from 2019 with notable shifting of serotype dominance to DENV-3 from DENV-2 in previous years. In our cohort, the prevailing age group was 1-20 years which is analogous with many studies in Asia. Conclusion: Dominance of DENV serotype shifted to DENV-3 in 2019 from prolonged persistence of DENV-2 and DENV-1. Continuous surveillance for circulating DENV serotype is needed for preparedness of potential outbreaks and occurrence of severe cases. Bangladesh J Med Microbiol 2021; 15 (2): 23-29